Maritime Independent Villages: A Form of Maritime Resilience Through Strengthening the Capacity of Coastal Communities in Ponipingan Village, Central Sulawesi - TOWADI, Mellisa; PAUWENI, Apriyanto A.J; T. MANDJO, Julius (International Journal of Environmental, Sustainability, and Social Science, 2024)
This article aims to disseminate service activities in the form of publications related to strengthening village capacity through waste management as a form of maritime resilience of Ponipingan village which is a coastal area of Bunobogu District, Buol Regency. The implementation of activities is carried out using counseling methods about the concept of the integration system "Desa Mandiri Maritim" or Maritime Independent Village” as a form of maritime resilience and training methods as a form of empowerment to the community. Articles are arranged in a qualitative normative manner based on data and the results of service activities that have been carried out. A series of maritime resilience concepts resulted in an increase in village capacity ranging from the community to the village apparatus.